PENGARUH LAYANAN BIMBINGAN KELOMPOK TERHADAP PENINGKATAN KONSEP DIRI SOSIAL SISWA YANG RENDAH KELAS X DI SMA NEGERI 2 TAMBANG TAHUN AJARAN 2015/2016 - Gasela Oktaviana; Raja Arlizon; Elni Yakub (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This research aims to know the influence of group guidance service against social self concept of students is low. This research was conducted from March 2016 to may 2016. Research methods used are real methods of experimental with pretest-posttest pattern control group design. The subjects of the research in this study are student of class X with low social self concept as much as 10 students. Data collection instrument used was the now are open. Data analysis technique used is a non parametric statistical techniques. Based on the results of a test of wilcoxon research hypothesis turns out to be accepted there is a difference of social self concept of students before and after the implementation of the guidance group group experiments. Next after compared between experimental group and the control group test results based on the mann-whitney, there is a significant difference in the concept of social group experiments with students in the control group. Spearman Rank test based on the influence of the tutoring service group towards the concept of social self that is 42.2%.